Properties of alkali activated lightweight aggregate generated from Sidoarjo Volcanic Mud (Lusi), fly ash, and municipal solid waste incineration bottom ash - Risdanareni, Puput (2020)
Production of artificial lightweight aggregate (LWA) from industrial by-products or abundant volcanic mud is a promising solution to prevent damaging the environment due to the mining of natural aggregate. However, improvements are still needed in order to control the high water absorption of LWA and strength reduction in resulting concrete or mortar. Hence in this research, fly ash, municipal solid waste incineration bottom ash (MSWI BA), and Sidoarjo volcanic mud (Lusi) were employed as a precursor and activated using NaOH 6 M and Na2SiO3 in producing LWA. The influence of the type of the precursors on the physical properties of resulting LWA was investigated. The effect of replacing natural fine aggregate with the resulting LWA on the compressive strength and volume density of mortar was also determined. Finer particles, a high amount of amorphous phase, and low loss on ignition (LOI) of the raw material improved the properties of resulting LWA. Mortar compressive strength was decreased by 6% when replacing 16% by volume of natural fine aggregate with fly ash based LWA. Compared to the expanded clay LWA, the properties of alternative LWAs in this study were slightly, but not significantly, inferior. Alternative LWA becomes attractive when considering that expanded clay LWA requires more energy during the sintering process.